2020
DOI: 10.1080/00313831.2020.1754901
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teachers, Parents, and Friends in Developing Adolescents’ Societal Interest

Abstract: This article examines the role of teachers, parents, and friends in stimulating the development of societal interest among adolescents. It assesses the extent teachers can compensate for societal interest differences among adolescents that arise due to socioeconomic differences. The YeS panel study is used, with 587 students aged 13-18 assessed annually over a sixyear period (2010-2015) and uses latent growth curve modeling (LGCM). Our findings indicate that awareness-raising by each of the three groups contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Therefore, the motivation for policy-makers is to maximise their achievement as they do strive to search until they find the one best alternative. (c) The conflict between natural choice and need in action: Policy-makers are not motivated to make decisions on the basis of societal goals, but they try to maximise their own reward, such as power; the time involved in realising a thorough analysis of the impending policy may be short during an emergency (Wanders, Dijkstra, Maslowski, Van Der Veen & Amnå, 2020); and, there are several conflicting values among specific groups and individuals that obstruct policy-makers from making an effective comparison of options. (d) The tendency of the deliverance of political feasibility: The model is concerned with what is possible; the probability that, however rational a policy option is, it does not mean that it will be acted upon.…”
Section: The Rational Model Of Policy Formulationmentioning
confidence: 99%
“…Therefore, the motivation for policy-makers is to maximise their achievement as they do strive to search until they find the one best alternative. (c) The conflict between natural choice and need in action: Policy-makers are not motivated to make decisions on the basis of societal goals, but they try to maximise their own reward, such as power; the time involved in realising a thorough analysis of the impending policy may be short during an emergency (Wanders, Dijkstra, Maslowski, Van Der Veen & Amnå, 2020); and, there are several conflicting values among specific groups and individuals that obstruct policy-makers from making an effective comparison of options. (d) The tendency of the deliverance of political feasibility: The model is concerned with what is possible; the probability that, however rational a policy option is, it does not mean that it will be acted upon.…”
Section: The Rational Model Of Policy Formulationmentioning
confidence: 99%
“…We argue that young citizens can be defined not only as engaged or unengaged, but they can simultaneously be distinguished between trustful and distrustful (Tzankova, 2018). Political and societal interest are considered crucial in characterizing youth who are involved latently (Ekman & Amnå, 2012) and are considered to be important groundwork for future participation (Prior, 2010; Russo & Stattin, 2017; Wanders et al, 2020). However, few studies have examined empirically typologies of youth citizenship defined by active participation and interest (Amnå & Ekman, 2014) and none, to our knowledge, have expanded them by including a dimension of trust or have analyzed them in multinational samples.…”
Section: The Present Studymentioning
confidence: 99%
“…The socio-ecological scientific prevention method, as well as other universal, and multimethod programs advocate approaching multiple levels, with the understanding that promoting the strengths of children, parents, and schools may lead to multiple positive outcomes [ 3 , 4 , 5 ]. In particular, parents and teachers play important roles in raising preadolescents’ awareness of self-care behaviors and social issues [ 6 ]. Indeed, previous research has reported that shared experiences between youth and parents increased the latter’s empathy for and understanding of their children’s experiences, thus helping them to gain positive outcomes from an educational program [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most educational institutions over the world suspended face-to-face teaching and went online, and thus youth’s routines were disrupted [ 14 , 15 ]. Studies point to the ramifications of online studying, demonstrating, for example, that these platforms lack crucial environmental contacts [ 6 ], such as peer interactions and personal communications with teachers in the school environments [ 16 ]. In addition, the forced isolation has come at the expense of peer group attachments, and consequently, individuals’ sense of self-esteem has been hampered [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%